Effectiveness of Oral Providing of Ajwa Date Fruit Extract on Malondialdehyde and Superoxide Dismutase Levels of White Rats Induced by Excessive Physical Activity - Jayanti, Herlina; Syahrian, Muhammad Faridz; Mukhtar, Zulfikri (Newinera Publisher, 2024)
Natural food ingredients are becoming increasingly popular as a treatment. According to studies and investigations, experts increasingly turn to natural remedies to treat disease, including date fruit extract (Phoenix dactylifera). This study tested the effectiveness of oral date palm fruit extract (Phoenix dactylifera) in reducing blood malondialdehyde levels in white rats (Rattus norvegicus) induced by excessive physical activity and increasing blood levels. Intense physical exercise increases white rat blood superoxide dismutase. This research is a laboratory experimental research or an actual experiment. The research design used a pre-test and post-test with a control group design to analyze the effectiveness of oral administration of date palm (Phoenix dactylifera) extract on the MDA and SOD levels of white rat (Rattus norvegicus) samples induced by excessive physical activity. The results of date fruit extract (Phoenix dactylifera) at 5 ml were more effective at reducing MDA and increasing SOD levels in white mice induced by excessive physical activity than at 3 and 4 ml. The experimental group treated with date fruit extract (Phoenix dactylifera) had lower MDA and higher SOD levels than the group given distilled water. Date fruit extract (Phoenix dactylifera) contains flavonoids and tannins. Some bioactive substances are antioxidants. Antioxidants can assist the body fight free radicals from excessive physical exertion.